2001
DOI: 10.1006/jmla.2000.2782
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Suppression and Enhancement in Understanding Metaphors☆

Abstract: Participants read either a metaphorical prime sentence, such as That defense lawyer is a shark, or they read a baseline-prime sentence. The baseline-prime sentence was literally meaningful in Experiment 1 (e.g., That large hammerhead is a shark), nonsensical in Experiment 2 (e.g., His English notebook is a shark), and unrelated in Experiment 3 (e.g., That new student is a clown). After reading the prime sentence, participants verified a target property statement. Verification latencies for property statements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
127
3
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(147 citation statements)
references
References 69 publications
13
127
3
4
Order By: Relevance
“…2 With respect to goals, for instance, Lutz and Radvansky (1997) observed that failed goal information remained more available than completed goal information and concluded that this was due to "both an increased availability of failed goal information and a decreased availability of completed goal information (relative to failed goal information)" (p. 308). Additional evidence has supported the notion that readers suppress irrelevant information during reading (e.g., Gernsbacher & Faust, 1991;Gernsbacher, Keysar, Robertson, & Werner, 2001;Linderholm et al, 2004). Therefore, it is possible that the outcome sentence in the control condition in these experiments might have led the reader away from thinking about the target spatial information because it was no longer relevant, decreasing its availability.…”
Section: Discussionmentioning
confidence: 60%
“…2 With respect to goals, for instance, Lutz and Radvansky (1997) observed that failed goal information remained more available than completed goal information and concluded that this was due to "both an increased availability of failed goal information and a decreased availability of completed goal information (relative to failed goal information)" (p. 308). Additional evidence has supported the notion that readers suppress irrelevant information during reading (e.g., Gernsbacher & Faust, 1991;Gernsbacher, Keysar, Robertson, & Werner, 2001;Linderholm et al, 2004). Therefore, it is possible that the outcome sentence in the control condition in these experiments might have led the reader away from thinking about the target spatial information because it was no longer relevant, decreasing its availability.…”
Section: Discussionmentioning
confidence: 60%
“…sharks are tenacious) but not sentences that refer to properties that are irrelevant to the metaphor's meaning (e.g. sharks are good swimmers; Gernsbacher, Keysar, Robertson, & Werner, 2001). Taken together, the aforementioned studies suggest that online metaphor comprehension hinges on accessing the appropriate sense of the vehicle.…”
Section: Semantics Metaphor Processingmentioning
confidence: 99%
“…Results testifying to the role of working memory and inhibitory control in understanding metaphorical content were also obtained by Blasko and Trich (1997;cited in Blasko, 1999), Monetta and Pell (2007), and Gernsbacher, Keysar, Robertson, and Werner (2001).…”
Section: Working Memory and Inhibitory Control In Metaphor Processingmentioning
confidence: 52%